Designing the Instrument of Aptitude and Interest for High School students - Ayu Nurhikmah; Erlin Fitria (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
The change of the free curriculum is learning to change the school's flow into a standardized elective group. Changes in flow are certainly made by guidance and counseling teachers. Guidance and counseling teachers need to update the instruments used for more comprehensive measurement of student interest and talents, while the instruments normally used by guidance and counseling teachers are interviews, sociometry, and talent interest tests that cooperate with the psychology society. It needs to be to develop more flexible talent instruments and interests to be used at school and low cost. The study aims to develop talent instruments and interests by using Microsoft excel. Microsoft excel is selected because it is relatively easy to use among teachers. The instrument's design has several menus, one of which is individual results, aspect analysis results, and results diagram. The benefits of this instrument designer are expected to be used at school to help guidance and counseling teachers identify the students' talents and interests and direct students to subject groups that match students' interests and talents.